Respuesta :
Answer: x=8.5 y=1.5
Step-by-step explanation:
Use the second problem and get X by itself. X= 5y+1. Now plug that equation into the 1st equation.
-(5y+1) +9y =-5.
-5y-1+9y=-5.
-5y+9y= 1+5
4y= 6
Y=1.5
Now that you know what is the value of Y you can plug that into any equation.
5(1.5) +1
7.5+1
X=8.5
For this case we have the following system of equations:
[tex]-x + 9y = -5\\x-5y = 1[/tex]
We clear "x" from the second equation and replace it in the first:
[tex]x = 1 + 5y[/tex]
Substituting in the first equation:
[tex]- (1 + 5y) + 9y = -5\\-1-5y + 9y = -5[/tex]
We have similar terms:
[tex]-1 + 4y = -5[/tex]
Adding 1 to both sides of the equation:
[tex]4y = -5 + 1\\4y = -4\\y = \frac {-4} {4}\\y = -1[/tex]
We look for the value of "x":
[tex]x = 1 + 5 (-1)\\x = 1-5\\x = -4[/tex]
Answer:
[tex](x, y): (- 4, -1)[/tex]